Supervision and Law Enforcement Efforts on Food Products Unfit for Consumption Based on Law Number 18 of 2012 concerning Food - Nurmala, Leni; Kodai, Dince Aisa; Ahmad, Ibrahim (PT. Riset Press International, 2023)
The problem in this research is how to monitor the circulation of products that are not suitable for consumption as a form of consumer protection for the public. The aim of this research is to provide knowledge to the public as consumers so that they are always careful and alert when consuming food products. The research method used in this writing is Normative Juridical research. A juridical approach that is based on existing legal regulations or legislation. The conclusion from this research is that there are still many food products circulating in the community that contain food preservatives, namely formaldehyde, borax and synthetic dyes Rhodamine B and Methanil Yelow, which are often used as textile dyes, food products that do not include production dates and expiration dates. With the circulation of products that are not suitable for consumption and can cause health problems, it is quite disturbing for the public, so to overcome this condition, the government must be able to carry out supervision and must impose sanctions on business actors who violate statutory provisions.